Sustainability through open innovation : Carlsberg and the Green Fiber Bottle - Chesbrough, Henry; Bogers, Marcel; Strand, Robert; Whalen, Elizabeth (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2018)
The case follows Danish brewer Carlsberg as it develops the Green Fiber Bottle, a beer bottle made of wood pulp, in collaboration with a startup, a small-to-medium sized enterprise (SME), and a Danish university. Sustainability was the primary motivator for the project, and open innovation was the primary development method. The case has a dual focus. First, it demonstrates how a company can successfully innovate by leveraging the concept of open innovation. Second, it shows how sustainability--and relatedly, the idea of purpose--can be a powerful motivator to drive open innovation efforts.
Originally Published InChesbrough, H., Bogers, M., & Whalen, E. (2018). Sustainability through open innovation: Carlsberg and the Green Fiber Bottle. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Technological innovations -- Management -- Case studies; Small business -- Case studies; Strategic planning -- Case studies